2018
DOI: 10.1136/neurintsurg-2018-014368
|View full text |Cite
|
Sign up to set email alerts
|

The most mentioned neurointervention articles in online media: a bibliometric analysis of the top 101 articles with the highest altmetric attention scores

Abstract: Background and purposeAlternative metrics (altmetrics), based on mentions in online media, is a new tool that can help to identify the most influential articles to diverse public audiences. This article aimed to determine the 100 most mentioned articles in the field of neurointervention and to analyze their characteristics.Materials and methodsWe selected the 808 journals that were considered journals potentially publishing articles on neurointervention. We also selected articles using keywords. Using the Altm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
31
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 23 publications
5
31
2
1
Order By: Relevance
“…In Table 3, the published item editorial was included, despite not being considered a study design, because it was able to attract considerable online attention and our aim was to identify every published item able to get a significant AAS. The results are similar to the ones reported in Altmetric studies performed in cardiovascular research, in Neurointervention, Endodontics, and Periodontics [10,23,26,27].…”
Section: Discussionsupporting
confidence: 90%
“…In Table 3, the published item editorial was included, despite not being considered a study design, because it was able to attract considerable online attention and our aim was to identify every published item able to get a significant AAS. The results are similar to the ones reported in Altmetric studies performed in cardiovascular research, in Neurointervention, Endodontics, and Periodontics [10,23,26,27].…”
Section: Discussionsupporting
confidence: 90%
“…This was consistent with previous studies exploring the association between altmetric indicators and citation numbers . A recent bibliometric analysis of neurointervention articles also suggested that AAS operates independently of citations and can be used as an alternative index for measuring an article's impact . Considering that attention itself does not reflect the quality of research, AAS might not represent the qualified impact in specialized academic fields; however, information will be no longer be inaccessible in the near future, and AAS, as a disseminative impact, might be a complementary indicator in the evaluation of the impact of a specific article …”
Section: Discussionsupporting
confidence: 87%
“…16,17 A recent bibliometric analysis of neurointervention articles also suggested that AAS operates independently of citations and can be used as an alternative index for measuring an article's impact. 18 Considering that attention itself does not reflect the quality of research, AAS might not represent the qualified impact in specialized academic fields; however, information will be no longer be inaccessible in the near future, and AAS, as a disseminative impact, might be a complementary indicator in the evaluation of the impact of a specific article. 4 In terms of the topic of all four bibliometrics, epidemiologic studies providing prevalence, regional antibiotics resistance profile, global eradication rate of H pylori, [19][20][21][22][23][24] or the risk of developing non-cardia gastric cancer by H pylori 25 were prevalent in the WoSCC or Google Scholar top-52 bibliometrics reflecting recent citations ( Table 1 and Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 A recent bibliometric analysis of neurointervention articles also suggested that AAS operates independently of citations and can be used as an alternative index for measuring an article's impact. 17 Considering that attention itself does not reflect the quality of research, AAS might not represent a qualified impact in specialized academic fields; however, information will no longer be inaccessible, and AAS, as a disseminative impact, might be a complementary indicator in the evaluation of the impact of a specific article.…”
Section: Discussionmentioning
confidence: 99%